2019
DOI: 10.1001/jamaoto.2018.4131
|View full text |Cite
|
Sign up to set email alerts
|

Patient Experience of Thyroid Cancer Active Surveillance in Japan

Abstract: IMPORTANCEThe burden of concern for patients with thyroid cancer who undergo surgical intervention with or without radioactive iodine is known to be substantial. For patients under active surveillance, this aspect of the patient experience has not been described to date and could be a potential barrier to broader acceptance of surveillance as a cancer management strategy.OBJECTIVE To describe the experiences of patients in the longest-standing and largest thyroid cancer active surveillance program. DESIGN, SET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 48 publications
1
72
0
9
Order By: Relevance
“…21,29 In addition to the optimization of inclusion and exclusion criteria, the anxiety or resistance of patients (or even physicians) during active surveillance is another valid consideration that is still being studied. 21,53,54 However, a complete explanation is very important in relieving patient fears. For this reason, it is important to provide information and education on this subject to physicians who interact with these patients.…”
Section: Optimal Management Of Papillary Thyroid Microcarcinomamentioning
confidence: 99%
“…21,29 In addition to the optimization of inclusion and exclusion criteria, the anxiety or resistance of patients (or even physicians) during active surveillance is another valid consideration that is still being studied. 21,53,54 However, a complete explanation is very important in relieving patient fears. For this reason, it is important to provide information and education on this subject to physicians who interact with these patients.…”
Section: Optimal Management Of Papillary Thyroid Microcarcinomamentioning
confidence: 99%
“…This also raises an interesting question as to whether the PTC found in neck nodes may have arisen from benign lateral aberrant thyroid tissue or is indeed metastatic disease from a true microscopic carcinoma, which is clinically and/or radiologically inapparent. With increasing evidence in the literature on the success of active surveillance programs for biopsy‐proven papillary microcarcinomas, it would be logical to consider these patients with true microscopic carcinomas in thyroid gland to be candidates for active surveillance . Thus, active surveillance of the thyroid and neck after adequate diagnostic work up (eg, thyroid ultrasound, CT scan, and/or PET‐CT) may be an effective strategy in appropriately selected patients.…”
Section: Discussionmentioning
confidence: 99%
“…With increasing evidence in the literature on the success of active surveillance programs for biopsy-proven papillary microcarcinomas, it would be logical to consider these patients with true microscopic carcinomas in thyroid gland to be candidates for active surveillance. 20,21 Thus, active surveillance of the thyroid and neck after adequate diagnostic work up (eg, thyroid ultrasound, CT scan, and/or PET-CT) may be an effective strategy in appropriately selected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Through a combination of patient surveys and interviews, they revealed that patients overall worry about cancer recurrence, metastases, and need for surgical intervention to a similar degree as patients who undergo surgery. 45 The proportion of patients who did not worry about their cancer outcomes steadily increased over the course of the surveillance period, and a large percentage of patients (83%) agreed that AS was the best management option for them. Additionally, and importantly, a large proportion of patients (77%) were not aware of AS as a treatment modality before it was offered to them.…”
Section: Contribution Of the Thyroid Surgeon To Shared Decision-makingmentioning
confidence: 99%
“…A study performed by Davies et al sought specifically to assess the experience of patients undergoing AS. Through a combination of patient surveys and interviews, they revealed that patients overall worry about cancer recurrence, metastases, and need for surgical intervention to a similar degree as patients who undergo surgery . The proportion of patients who did not worry about their cancer outcomes steadily increased over the course of the surveillance period, and a large percentage of patients (83%) agreed that AS was the best management option for them.…”
Section: Introductionmentioning
confidence: 99%